Pirt Licensing Assistance and Halal Certification of Snack Products for SMEs in Panembahan Village, Plered District, Cirebon District - Amir Macmud; Bustaman (Asian Journal of Community Services, 2022)
Pirt licensing and halal certification in the village of Panembahan, Plered, Cirebon. This PKM aims to increase the understanding of food and beverage SMEs in the village of Panembahan, Plered, Cirebon, about the importance of pirt licensing and halal certification to increase the selling value of products and also consumer buying interest. The implementation of this PKM is carried out using lecture, tutorial, and discussion methods. The results of this PKM program are (1) SMEs understand the importance of pirt licensing and halal certification, and are motivated to continue it, (2) SMEs understand the procedures for pirt licensing, and (3) SMEs understand the procedures for halal certification. Thus, consumer buying interest and consumer trust are expected to increase through the presence of pirt numbers and halal labels. besides that it is also expected to increase product sales and the welfare of the people in Panembahan Village, Plered, Cirebon.